Improvement of Transfer Wheel Marker Design Using the Quality Function Deployment (QFD) Method for School Field Line Marking - Roslan, Yasmin Syaliana; Hassan, Mohd Fahrul; Hamdan, Izza; Tuparman, Mohd Hafiz (Journal of Advanced Mechanical Engineering Applications, 2023)
The line marking of sports fields is a must-do activity in every school in Malaysia since most of the schools only have one field that is used for many sports activities. There are many concept designs of sport line markings in the market, but the most common design used in Malaysia is a transfer wheel marker. However, the machine lacks many aspects, including clogging problems due to the loose grass, soil sticking to the marker wheel, and its unstable tyre, which may cause the line marking process time becomes longer and more difficult. Therefore, this study proposes to improve the design of the transfer wheel marker using the Quality Function Deployment (QFD) method. Based on the QFD method, a House of Quality (HoQ) in the first phase was applied, where a questionnaire was created using the information obtained from interviews with school teachers to quantify the needs. The collected data was then analyzed in the HoQ to determine the final ranking of engineering characteristics. With a relative weight of 14.45%, the handle height is ranked first as the characteristic that needs improvement. The second ranking order is the amount of wasted paint at 14.08% and the third ranking is tyre friction which is 11.86% relative weight. Hence, the identified three priority components will lead to the improvement of the transfer wheel marker design.